Activation of the Cap'n'collar C pathway (Nrf2 pathway in vertebrates) signaling in insulin pathway compromised Drosophila melanogaster flies ameliorates the diabetic state upon pro-oxidant conditions. - Álvarez-Rendón, J.P.; Riesgo-Escovar, J.R. (General and Comparative Endocrinology, 2023)
The insulin pathway is a crucial central system for metabolism and growth. The Nrf2 signaling pathway functions to counteract oxidative stress. Here we sought to study the consequences of an oxidative stress challenge to insulin compromised and control adult flies of different ages, varying the activation state of the Nrf2 pathway in flies, the Cap'n'collar C pathway. For this, we employed two different pro-oxidative conditions: 3 % hydrogen peroxide or 20 mM paraquat laced in the food. In both cases, wild type (control) flies die within a few days, yet there are significant differences between males and females, and also within flies of different ages (seven versus thirty days old flies). We repeated the same conditions with young (seven days old) flies that were heterozygous for a loss-of-function mutation in Keap1. There were no significant differences. We then tested two hypomorphic viable conditions of the insulin pathway (heteroallelic combination for the insulin receptor and the S6 Kinase), challenged in the same way: Whereas they also die in the pro-oxidant conditions, they fare significantly better when heterozygous for Keap1, in contrast to controls. We also monitored locomotion in all of these conditions, and, in general, found significant differences between flies without and with a mutant allele (heterozygous) for Keap1. Our results point to altered oxidative stress conditions in diabetic flies. These findings suggest that modest activation of the Cap'n'collar C pathway may be a treatment for diabetic symptoms.